An Analysis Of Mathematical Literacy Skills In Solving Pisa Mathematics Problems Among Students - Santiwidia, Arwini; Arjudin; Kurniawan, Eka; Prayitno, Sudi (Sigma&Mu: Journal of Mathematics Education, Mathematics, Statistics and Data Science, 2026)
This study aims to analyze mathematical literacy skills in solving PISA mathematics questions based on the level of mathematical literacy skills among students at SMPN 13 Mataram in the 2024/2025 academic year. This is a descriptive qualitative study involving 52 students from classes IX A and IX B, with 8 students selected as subjects. The research instruments used were a mathematics literacy test adapted from PISA and interview guidelines. Data were analyzed based on mathematics literacy process indicators (formulate, employ, interpret). The results showed that out of the 6 levels of mathematical literacy, no students reached levels 5 and 6. At level 1, students could formulate explicit information and solve problems using simple algorithms, at level 2, they could identify implicit information and select basic strategies to solve problems; at level 3, they could process complex explicit information containing distractors and develop sequential strategies for decision-making, while Level 4 can formulate explicit information in everyday contexts and apply strategies to complex concrete situations. Students at Levels 1-4 also have the ability to interpret and draw conclusions based on the context of the problem.